2022
DOI: 10.1101/2022.01.18.476748
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The two-component system ChvGI maintains cell envelope homeostasis in Caulobacter crescentus

Abstract: Two-component signal transduction systems (TCS) are often used by bacteria to rapidly assess and respond to environmental changes. ChvG/ChvI is a TCS conserved in α-proteobacteria and known for regulating expression of genes related to exopolysaccharide production, virulence and growth. The sensor kinase ChvG autophosphorylates upon yet unknown signals and phosphorylates the response regulator ChvI to activate transcription. Recent studies in Caulobacter crescentus showed that chv mutants are sensitive to vanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 59 publications
4
10
0
Order By: Relevance
“…However, previous studies found no common response to stresses including osmotic stress, heat shock, and low pH in A. tumefaciens [43]. Overall, the data presented here are in agreement with recent works in Caulobacter [35,42] which suggest that ChvGI activation is important in oligotrophic free-living bacteria as a cell envelope or osmotic stress response.…”
Section: Transcriptome Changes During Pbp1a Depletion Mimic Activatio...supporting
confidence: 92%
See 4 more Smart Citations
“…However, previous studies found no common response to stresses including osmotic stress, heat shock, and low pH in A. tumefaciens [43]. Overall, the data presented here are in agreement with recent works in Caulobacter [35,42] which suggest that ChvGI activation is important in oligotrophic free-living bacteria as a cell envelope or osmotic stress response.…”
Section: Transcriptome Changes During Pbp1a Depletion Mimic Activatio...supporting
confidence: 92%
“…The increased sensitivity to mecillinam, vancomycin, cefsulodin, and moenomycin in ChvGI mutants suggests that this pathway may confer resistance to antibiotics inhibiting cell wall synthesis [35]. Our observation that the depletion of A.…”
Section: Transcriptome Changes During Pbp1a Depletion Mimic Activatio...mentioning
confidence: 66%
See 3 more Smart Citations